Classroom Distraction as a Pedagogical Barrier and its Remedies - Sigdel, Surya (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
This paper explores the causes of classroom distraction and the ways to reduce them and promote students’ active participation . The main purpose of the study was to pursuit the ways to encourage learners’ self-efficacy and capability . In this hermeneutic phenomenological study, data were collected through in-depth interview, focus group discussion and classroom observation . The sources of the information were grade eight students and their teachers teaching English and social studies from five community schools of suburban area of Kathmandu . The schools and participants were selected using convenient and quota sampling respectively . The study found out that teacher centered activities are the main cause of distraction; furthermore, classroom environment, the students’ own and their peers’ behavior and attitude, teacher’s teaching strategies and their inept behavior, learning content and assessment have influenced the distraction . Until and unless, the concern authority disheartens pedagogical barriers and makes teachers accountable, the change seems impossible . Selection of learning content from students’ interest, use of assessment as a process of learning, gradual shift of pedagogy into heutagogy and teachers’ strategical classroom mobilization promote students’ engagement . It concludes that student friendly action-packed classroom activities which are enriched with learning content are the keys for the promotion of student participation.